Comparative evaluation of prophylactic single-dose intravenous antibiotic with postoperative antibiotics in elective urologic surgery - Mohammad K Moslemi; Seyed M Moosavi Movahed; Akram Heidari; et al (Dove Medical Press, 2010)
Mohammad K Moslemi1, Seyed M Moosavi Movahed2, Akram Heidari3, Hossein Saghafi2, Mehdi Abedinzadeh41Department of Urology, 2Department of Nephrology, 3Department of Health, Kamkar Hospital, Qom University of Medical Sciences, Qom, Iran; 4Department of Urology, Moradi Hospital, School of Medicine, Rafsanjan University of Medical Sciences, Rafsanjan, IranBackground: Unrestricted antibiotic use is very common in Iran. As a result, emergence of resistant organisms is commonplace. Antibiotic prophylaxis in surgery consists of a short antibiotic course given immediately before the procedure in order to prevent development of a surgical site infection. The basic principle of prophylaxis is to maintain effective concentrations of an antibiotic active against the commonest pathogens during the entire surgery.Materials and methods: We prospectively investigated 427 urologic surgery cases in our department between August 2008 and September 2009 (Group1). As reference cases, we retrospectively reviewed 966 patients who underwent urologic surgery between May 2004 and May 2008 (Group 2) who were administered antibiotics without any restriction. Prophylactic antibiotics such as cefazolin were administered intravenously according to our protocol. Postoperative body temperature, peripheral white blood cell counts, urinalysis, and urine culture were checked.Results: To judge perioperative infections, wound condition and general condition were evaluated in terms of surgical site infection, as well as remote infection and urinary tract infection, up to postoperative day 30. Surgical site infection was defined as the presence of swelling, tenderness, redness, or drainage of pus from the wound, superficially or deeply. Remote infection was defined as occurrence of pneumonia, sepsis, or urinary tract infection. Perioperative infection rates (for surgical site and remote infection) in Group 1 and Group 2 were nine of 427 (2.6%) and 24 of 966 (2.5%), respectively. Surgical site infection rates of categories A and B in Group 1 were 0 and two (0.86%), respectively, while those in Group 2 were 0 and five (0.92%), respectively. There was no significant difference in infection rates in terms of remote infection and surgical site infection between Group 1 and Group 2 (P = 0.670). The amounts, as well as the prices, for intravenously administered antibiotics decreased to approximately one quarter.Conclusion: Our protocol effectively decreased the amount of antibiotics used without increasing perioperative infection rates. Thus, our protocol of prophylactic antibiotic therapy can be recommended as an appropriate method for preventing perioperative infection in urologic surgery. Keywords: surgical site infection, antibiotic prophylaxis, single dose, urologic surgery